Child Protection in the Perspective of Islamic Family Law by Era Digital - Banurea, Sabarite (Teunuleh Publisher, 2025)
The digital era has brought significant changes in parenting patterns, where children are now vulnerable to various online threats such as negative content, cyberbullying, and digital exploitation. In this context, Islamic family law needs to be reviewed to answer the challenges of the times. This research uses a normative qualitative approach with a literature study of classical and contemporary Islamic legal sources, the Child Protection Law, and the Compilation of Islamic Law. The analysis was carried out descriptive-analytically with the maqashid al-shari'ah approach. Islamic family law has the principle of child protection through the concept of hadanah, maqashid al-shari'ah, and the moral responsibility of parents. However, the existing legal framework has not explicitly accommodated digital issues. Child protection in the digital era requires a reinterpretation of Islamic legal values, sharia-based digital literacy strategies, and the integration of Islamic values into national child protection policies. Islamic family law has great potential as an ethical and normative solution to the challenges of digital child protection, as long as it is actualized contextually and applicatively.